1985
DOI: 10.1007/bf00266514
|View full text |Cite
|
Sign up to set email alerts
|

Cefuroxime in CMW bone cement

Abstract: This paper presents the results of adding the antibiotic cefuroxime to CMW bone cement in a group of patients undergoing total hip or knee replacement, in which the levels of cefuroxime were assayed in the blood, wound drainage fluid, urine and surplus bone cement. It was found that very small amounts of cefuroxime, less than 5%, were recovered in the urine, serum and drainage fluid in the first week following operation, and since it is known that cefuroxime is not metabolised or excreted elsewhere in the body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The strengths of this study are that all results are expressed in quantities. Most authors express their results as concentrations (Innes et al 1985;Vielpeau et al 1980;Wahlig et al 1984) and neglect volumes of drainage fluids and urine. These factors cause inexact or imprecise estimates of blood kinetics and bioavailability.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The strengths of this study are that all results are expressed in quantities. Most authors express their results as concentrations (Innes et al 1985;Vielpeau et al 1980;Wahlig et al 1984) and neglect volumes of drainage fluids and urine. These factors cause inexact or imprecise estimates of blood kinetics and bioavailability.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies of this topic (Innes et al 1985;Wahlig et al 1984) expressed data mainly in terms of antibiotic concentration. Such an approach is not suitable for evaluation of bioavailability of a drug in bone cement.…”
mentioning
confidence: 98%
“…16,38 Their studies showed effective prophylaxis of infection after total joint replacement by cefuroxime in bone cement. The effect of cefuroxime on the mechanical property of cement had been discussed before.…”
Section: Discussionmentioning
confidence: 98%
“…However, despite this, cefuroxime is still a commonly-used prophylactic antibiotic for joint replacement surgery in the UK and has been extensively studied. [25][26][27][28] Patterns of bacterial resistance vary with both time 29 and location. 30,31 However, since 95% of our isolates were sensitive to gentamicin, it seems appropriate to continue the use of this agent in the bone cement used at THA.…”
Section: Discussionmentioning
confidence: 99%